You Saw Me on the Radio : Recollections and Favorite Calls as the Voice of Aggie Athletics - South, Dave (Book collections on Project MUSE., 2019)
"For 48 years, Dave South was the radio voice of Southwest Conference and Texas A & M University football, basketball, and baseball. Along the way, he amassed a treasure trove of unforgettable stories, anecdotes, and conversations with noteworthy personalities, both on and off the field. In You Saw Me on the Radio, he collects some of his favorite stories from the broadcast booth, locker room, and other behind-the-scenes locations. This collection of lively tales is organized around themes such as "Memorable Games," "Players," "Interviews," "Goofs," and "Fans." These good-natured recollections of a long and colorful career are accompanied by a gallery of photographs gathered from South's interactions with Aggie sports greats, iconic venues, and other people, places, and events that have created treasured sports memories over almost five decades. With a wink and a generous dose of self-deprecating humor, Dave relates some of his most embarrassing gaffes and miscues, including the time he conducted an awkward interview with the Treasurer of the United States-while having no idea who she was or what she did. He tells about the infamous "yellow spot" on Kyle Field. He reveals the truth behind "beanie weenies," the culinary secret weapon of Texas A & M football recruiters. And of course, South pays heartfelt tribute to the coaches, players, fans, and fellow broadcasters who became his friends through the years. Loaded with accounts of unforgettable contests, hilarious moments, and poignant memories, You Saw Me on the Radio is sure to be a favorite for fans of Texas A & M University athletics and sports lovers everywhere"--